Risk Factors for the Presence of Aedes aegypti and Aedes albopictus in Domestic Water-Holding Containers in Areas Impacted by the Nam Theun 2 Hydroelectric Project, Laos - Hiscox, Alexandra (The American Society of Tropical Medicine and Hygiene, 2013)
We assessed risk factors for vectors of dengue and chikungunya viruses near a new hydroelectric project, Nam Theun 2, in Laos. Immature stages of Aedes aegypti were found only in sites within 40 km of the urban provincial capital, but Aedes albopictus was found throughout. Aedes aegypti pupae were most common in water storage jars (odds ratio [OR] = 4.72) and tires (OR = 2.99), and Ae. albopictus pupae were associated with tires in 2009 (OR = 10.87) and drums, tires, and jars in 2010 (drums OR = 3.05; tires OR = 3.45, jars OR = 6.59). Compared with water storage vessels, containers used for hygiene, cooking, and drinking were 80% less likely to harbor Ae. albopictus pupae in 2010 (OR = 0.20), and discarded waste was associated with a 3.64 increased odds of infestation. Vector control efforts should focus on source reduction of water storage containers, particularly concrete jars and tires.